2013
DOI: 10.1002/dneu.22128
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of SHANK genes in neuropsychiatric disorders

Abstract: The genetic heterogeneity of neuropsychiatric disorders is high, but some pathways emerged, notably synaptic functioning. A large number of mutations have been described in genes such as neuroligins, neurexins, and SHANK that play a role in the formation and the maintenance of synapses. This review focuses on the disorders associated with mutations in SHANK3 and the other members of its family, SHANK1 and SHANK2. SHANKs are scaffolding proteins of the postsynaptic density of glutamatergic synapses. SHANK3 has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
182
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(191 citation statements)
references
References 61 publications
(80 reference statements)
3
182
2
4
Order By: Relevance
“…This gene has been identified in patients with ASD and ID [36,37]. In our study, no difference in the mRNAs of SHANK2 in ADHD, ASD, and ID was present, with the increased expression of SHANK2-targeting lncRNA in ASD, which may reflect a different expression pattern in different cells for SHANK2.…”
Section: Differential Expression Of Lncrnas and Targeted Mrnas Of Bdncontrasting
confidence: 42%
“…This gene has been identified in patients with ASD and ID [36,37]. In our study, no difference in the mRNAs of SHANK2 in ADHD, ASD, and ID was present, with the increased expression of SHANK2-targeting lncRNA in ASD, which may reflect a different expression pattern in different cells for SHANK2.…”
Section: Differential Expression Of Lncrnas and Targeted Mrnas Of Bdncontrasting
confidence: 42%
“…Consistent with the IPA results, gene ontology analysis using EASE (DAVID) [28] shows that both modules are significantly enriched for functions related to nervous system and neuron development, synaptic transmission and calcium ion binding (Table S12 in Additional file 1). An analysis of co-methylation networks between the top-ranked 'hub' probes in the black and pink modules shows that they are connected by DNA methylation in the vicinity of SHANK2, a molecular scaffold protein that plays a critical role in neurodevelopment and synaptogenesis, and has been widely implicated in several neurodevelopmental disorders, including schizophrenia [29] ( Figure 2D). Furthermore, several of the probes are located in genes that have been strongly Other examples of schizophrenia-associated DMPs correlated with neocortical development are shown in Figure S6 and Table S13 in Additional file 1. implicated in schizophrenia by a recent large collaborative genome-wide association study (GWAS; for example, CACNA1C, TSNARE1, PITPNM2, and HLA-L) [27].…”
Section: Resultsmentioning
confidence: 99%
“…Although syndromic ASD has been estimated to account for only 5 to 25 % of all cases of ASD (Adviento et al 2014;de la Torre-Ubieta et al 2016;Jeste and Geschwind 2014), more forms of syndromic ASD continue to be identified (Adviento et al 2014;Richards et al 2015;Roullet et al 2013;Smile et al 2013;Yu and Berry-Kravis 2014;Yuen et al 2015). In addition, syndromic and idiopathic ASD brain impairments have been reported that are similar (Adviento et al 2014;Blackmon 2015;D'Angelo et al 2015;Guilmatre et al 2014;Klusek et al 2015;Sala et al 2015).…”
Section: Does Asd Have Neurobiological Validity?mentioning
confidence: 99%